Application of Geospatial Techniques for Groundwater Quality and Availability Assessment: A Case Study in Jaffna Peninsula, Sri Lanka - Gunaalan, K; Ranagalage, M; Gunarathna, M. H. J. P.; Vithanage, M (My University, 2018)
Groundwater is one of the most important natural resources in the northern coastal belt of Sri Lanka, as there are no major water supply schemes or perennial rivers. Overexploitation, seawater intrusion and persistent pollution of this vital resource are threatening human health as well as ecosystems in the Jaffna Peninsula. Therefore, the main intent of the present paper is to apply geospatial techniques to assess the spatial variation of groundwater quality and availability for the sustainable management of groundwater in the coastal areas. The electrical conductivity (EC) and depth to water (DTW) of 41 wells were measured during the period from March to June 2014, which represents the dry period of the study area. Surface interpolation, gradient analysis, a local indicators of spatial autocorrelations (LISA) and statistical analysis were used to assess the quality and availability of groundwater. The results revealed that the drinking and irrigation water quality in the study area were poor and further deteriorated with the progression of the dry season. Good quality and availability of groundwater were observed in the western zone compared to other zones of the study area. A negative correlation was identified between depth to water and electrical conductivity in the western zone. Hence, relatively deep wells in the western zone of the study area can be used to utilize the groundwater for drinking, domestic and agricultural purposes. The outcomes of this study can be used to formulate policy decisions for sustainable management of groundwater resources in Jaffna Peninsula.
Keywords: electrical conductivity; gradient analysis; interpolation; local indicators of spatial autocorrelations; groundwater; depth towater; Jaffna Peninsula